Encapsulation of Mucuna pruriens seed extract using nanocellulose and its evaluation for Parkinson's treatment - Ratnaningsih Eko Sardjono; Ramdhan Gunawan; Asep Kadarohman; Budiman Anwar; Hamidie Ronald Daniel Ray; Suci Nur Vikasari; Erdiwansyah; Siti Fatimah; Young Gun Ko (JCIS Open, 2025)
Mucuna pruriens (MP), a natural source of L-DOPA, holds potential as a Parkinson's disease (PD) treatment. This study developed two encapsulation systems for MP using nanocellulose (NC-MP) and nanocellulose-chitosan-tripolyphosphate (NCT-MP) to enhance therapeutic efficacy. The encapsulation process was performed via ultrasonication and characterized by FTIR, SEM, and TEM, revealing polydisperse spherical particles with sizes of 566.37 ± 37.41 nm (NC-MP) and 756.66 ± 51.44 nm (NCT-MP). The anti-parkinsonian effects were evaluated in a catalepsy-induced mouse model using the horizontal bar test. Both encapsulated systems significantly reduced catalepsy duration (∗p∗ < 0.001). NC-MP demonstrated superior efficacy at low doses (5–20 mg/kg), attributed to its smaller particle size and neutral charge, which may facilitate blood-brain barrier penetration. In contrast, NCT-MP showed enhanced effects at 25 mg/kg, likely due to chitosan's cationic charge promoting active transport and tripolyphosphate-mediated matrix stabilization. These findings highlight the potential of encapsulation systems to optimize MP's therapeutic profile, with formulation efficacy dependent on dosage requirements.